Determinants of the cytosolic turnover of mitochondrial intermembrane space proteins - Kowalski, Lukasz (BMC Biol, 2018)
BACKGROUND: The proteome of mitochondria comprises mostly proteins that originate as precursors in the cytosol. Before import into the organelle, such proteins are exposed to cytosolic quality control mechanisms. Multiple lines of evidence indicate a significant contribution of the major cytosolic protein degradation machinery, the ubiquitin-proteasome system, to the quality control of mitochondrial proteins. Proteins that are directed to the mitochondrial intermembrane space (IMS) exemplify an entire class of mitochondrial proteins regulated by proteasomal degradation. However, little is known about how these proteins are selected for degradation. RESULTS: The present study revealed the heterogeneous cytosolic stability of IMS proteins. Using a screening approach, we found that different cytosolic factors are responsible for the degradation of specific IMS proteins, with no single common factor involved in the degradation of all IMS proteins. We found that the Cox12 protein is rapidly degraded when localized to the cytosol, thus providing a sensitive experimental model. Using Cox12, we found that lysine residues but not conserved cysteine residues are among the degron features important for protein ubiquitination. We observed the redundancy of ubiquitination components, with significant roles of Ubc4 E2 ubiquitin-conjugating enzyme and Rsp5 E3 ubiquitin ligase. The amount of ubiquitinated Cox12 was inversely related to mitochondrial import efficiency. Importantly, we found that precursor protein ubiquitination blocks its import into mitochondria. CONCLUSIONS: The present study confirms the involvement of ubiquitin-proteasome system in the quality control of mitochondrial IMS proteins in the cytosol. Notably, ubiquitination of IMS proteins prohibits their import into mitochondria. Therefore, ubiquitination directly affects the availability of precursor proteins for organelle biogenesis. Importantly, despite their structural similarities, IMS proteins are not selected for degradation in a uniform way. Instead, specific IMS proteins rely on discrete components of the ubiquitination machinery to mediate their clearance by the proteasome. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12915-018-0536-1) contains supplementary material, which is available to authorized users.